Developing and using matrix methods for analysis of large longitudinal qualitative datasets in out-of-home-care research - Hodgson, David; Cordier, Reinie; Parsons, Lauren; Walter, Bronte; Chikwava, Fadzai; Watts, Lynelle; Thoresen, Stian; Martinez, Matthew; Chung, Donna (Taylor & Francis, 2022)
Managing and analysing large qualitative datasets pose a particular challenge for researchers seeking a consistent and rigorous approach to qualitative data analysis. This paper describes and demonstrates the development and adoption of a matrix tool to guide the qualitative data analysis of a large sample (N = 122) of interview data. The paper articulates the theoretical and conceptual underpinnings of the matrix analysis tool and how it was developed and applied in a longitudinal mixed methods out-of-home-care research study. Specific illustrations and examples of data integration and data analysis are provided to demonstrate the benefits and potentials of constructing matrix tools to guide research teams when working with large qualitative data sets alone or in combination with quantitative data sets.